2014
DOI: 10.1021/ja506351f
|View full text |Cite
|
Sign up to set email alerts
|

Extended String Binding Mode of the Phosphorylated Transactivation Domain of Tumor Suppressor p53

Abstract: The transactivation domain (TAD) of tumor suppressor p53 has homologous subdomains, TAD1 and TAD2. Both are intrinsically disordered in their free states, but all structures of TAD1 and TAD2 bound to their target proteins have demonstrated use of an amphipathic α-helix, suggesting that the binding-coupled helix folding mechanism of TAD1 and TAD2 is essential. Although phosphorylation of TAD is important to switch the function of p53, bound structures of phosphorylated TAD1 and TAD2 have not been determined. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 63 publications
3
70
0
Order By: Relevance
“…A similar AD2 structure is observed in the complex with HMGB1, although the helix is somewhat shorter (64). Somewhat surprisingly, given the strong propensity of AD2 to fold into a helix, a doubly phosphorylated p53 AD2 motif binds in a more extended conformation to a highly electropositive region of the PH domain of human TFIIH p62 (65).…”
Section: Discussionmentioning
confidence: 63%
“…A similar AD2 structure is observed in the complex with HMGB1, although the helix is somewhat shorter (64). Somewhat surprisingly, given the strong propensity of AD2 to fold into a helix, a doubly phosphorylated p53 AD2 motif binds in a more extended conformation to a highly electropositive region of the PH domain of human TFIIH p62 (65).…”
Section: Discussionmentioning
confidence: 63%
“…In addition to XPC, the p62 PH domain binds to an acidic domain of the general transcription factor TFIIEa Okuda et al, 2008), the transactivation domain (TAD) of the tumor suppressor p53 (Di Lello et al, 2006;Okuda and Nishimura, 2014). Although various partners of the p62 PH domain have been identified (Di Lello et al, 2005;Iyer et al, 1996;Mas et al, 2011), only two tertiary structures of the human p62 PH domain bound to the TFIIEa acidic domain (Okuda et al, 2008) and phosphorylated p53 TAD (Okuda and Nishimura, 2014) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al demonstrated that the transactivation domain 2 of p53 protein forms a complex with CREB binding protein, and that a salt bridge between D49 of p53 protein and R2105 of nuclear coactivator binding domain of CREB binding protein may contribute to the binding specificity (11). Okuda and Nishimura suggested that the transactivation domain 2 of p53 protein binds the human TFIIH subunit p62 in an extended string-like conformation; they claimed that two phosphorylation sites, S46 and T55, play an important role (14) . It is worth noting that D49 locates between these amino acids.…”
mentioning
confidence: 99%